Management of Inactive Dynamic Archives in an Effort to Support Information Services at the Padang District Court Class 1A - Mulyandi, Afifah; Nabila, Jeihan (Scinary, 2024)
The management of inactive dynamic archives at the Padang District Court Class 1A already has procedures that include recording, controlling, distributing, storing, maintaining, supervising, transferring, and destroying archives. However, there are challenges in the form of limited storage capacity and less than optimal maintenance of archives. In addition, the absence of implementation of archive reduction and destruction has resulted in the accumulation of unused archives. Effective and systematic archive management is needed so that information and physical archives are maintained, supporting archive information services. Currently, the Padang District Court Class 1A only provides file boxes to store inactive archives that are lying in piles.